UTILIZATION OF UNCONTROLLED BURNT RICE HUSK ASH IN SOIL IMPROVEMENT - Agus Setyo Muntohar (Institute of Research and Community Outreach - Petra Christian University, 2002)
Expansive soil has been a problem in Indonesia as in other countries. Current research found that there is a potential use of silica waste%2C resulting from burnt rice husk%2C as a pozzolanic material. This paper presents the results of study on the utilisation of ashes produced from uncontrolled rice husk burnt in Yogyakarta %28Indonesia%29.%0D%0A%0D%0AIn this research%2C a series of laboratory tests has been conducted. The tests were carried out individually or in a combination in which the Rice Husk Ash %28RHA%29 content were varied from 7.5%2C 10%2C and 12.5 percent%2C and the lime content from 2%2C 4%2C 6%2C and 10 percent %28by the dry weight of soil%29. All the samples have been remoulded at their optimum moisture content %28OMC%29 and maximum dry density %28MDD%29. The research shows that lime - rice husk ash decreased the swell of expansive soil and improved its strength and bearing capacity.%0D%0A Abstract in Bahasa Indonesia : soil+improvement%2C+expansive+soil%2C+uncontrolled+-+burnt%2C+rice+husk+ash.